Book Review: Antony, Robert J. Like Froth Floating on the Sea: The World of Pirates and Seafarers in Late Imperial South China. Berkeley: Institute of East Asia Studies, University of California Press, 2003. Xiii, 198 pp. - Phumplab, Morragotwong (วารสารศิลปศาสตร์ มหาวิทยาลัยธรรมศาสตร์, 2023)
-